2017
DOI: 10.1038/srep46553
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of Plasmopara viticola and insight into the pathogenic mechanism

Abstract: Plasmopara viticola causes downy mildew disease of grapevine which is one of the most devastating diseases of viticulture worldwide. Here we report a 101.3 Mb whole genome sequence of P. viticola isolate ‘JL-7-2’ obtained by a combination of Illumina and PacBio sequencing technologies. The P. viticola genome contains 17,014 putative protein-coding genes and has ~26% repetitive sequences. A total of 1,301 putative secreted proteins, including 100 putative RXLR effectors and 90 CRN effectors were identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 93 publications
(151 reference statements)
3
77
0
Order By: Relevance
“…It is suggested that the RXLR‐dEER motif is involved in translocating effector proteins from haustoria into host cells (Dou et al , ; Kale et al , ). RXLR effectors have become a focus for studying plant–pathogen interaction in the past decade, with numerous effector genes identified and characterized in Phytophthora and downy mildew species (Tyler et al , ; Haas et al , ; Baxter et al , ; Yin et al , ). Many studies have reported that RXLR effectors are involved in the suppression of PTI and/or ETI (Wang et al , ; Kong et al , ; Fan et al , ) Additionally, some of them can trigger immune response‐related cell death, for example Phytophthora sojae Avh238 (Yang et al , ), Phytophthora capsici Avh1 (Chen et al , ), and Plasmopara viticola RXLR16 (Xiang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that the RXLR‐dEER motif is involved in translocating effector proteins from haustoria into host cells (Dou et al , ; Kale et al , ). RXLR effectors have become a focus for studying plant–pathogen interaction in the past decade, with numerous effector genes identified and characterized in Phytophthora and downy mildew species (Tyler et al , ; Haas et al , ; Baxter et al , ; Yin et al , ). Many studies have reported that RXLR effectors are involved in the suppression of PTI and/or ETI (Wang et al , ; Kong et al , ; Fan et al , ) Additionally, some of them can trigger immune response‐related cell death, for example Phytophthora sojae Avh238 (Yang et al , ), Phytophthora capsici Avh1 (Chen et al , ), and Plasmopara viticola RXLR16 (Xiang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Read alignment to the V. vinifera genome resulted in 70 to 90 % of reads that could be mapped onto the grapevine genome (Fig 3.). A second alignment of reads was performed to the P. viticola genome, which has been recently published (45), to check the presence or absence of P. viticola genes. For the 10d treatment between 25 to 35 % of reads from control samples mapped to the P. viticola genome, while only 1-4 % of reads from the treated plants mapped to the P. viticola genome.…”
Section: Resultsmentioning
confidence: 99%
“…Cleaned reads were first mapped against predicted mRNAs (PN40024 12X v2 grape reference transcriptome) obtained from the gene prediction version 2.0 of NCBI. Reads were also mapped to the P. viticola genome available at DDBJ/ENA/GenBank under the accession MTPI00000000 (45), to check presence or absence of the fungi inside the leaves.…”
Section: Methodsmentioning
confidence: 99%
“…This assembly is more complete (95.7% of expected BUSCO genes, Alveolata-Stramenopiles dataset, Supplementary table 2) than previous drafts generated with short reads only (Dussert et al 2016;Brilli et al 2018) or with a hybrid approach in which long reads were used for scaffolding (Yin et al 2017). The assembly was also more continuous, resolving many of the repetitive regions (Supplementary figure 1).…”
Section: A New High-quality Pl Viticola Genome Assemblymentioning
confidence: 93%